2005
DOI: 10.1021/bi050018s
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like factor 2 Transcriptional Regulation Involves Heterogeneous Nuclear Ribonucleoproteins and Acetyltransferases

Abstract: Kruppel-like factor 2 (KLF2) is expressed in several cell types, and knockout animals have shown that KLF2 gene regulation is involved in multiple biological processes. These include maintaining T-cells in the quiescent state, preventing preadipocytes from differentiating into mature adipocytes, stabilizing blood vessel walls through endothelial cell function, and advancing the later stages of lung development. Defining the regulation of KLF2 expression is important to understand these diverse functions. Promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
3
29
0
Order By: Relevance
“…It has been proposed that KLF2 can bind p300 and compete with phosphorylated NF-B p65 antagonizing NF-B transcriptional activity. 8,10,32 Our ChIP data are not fully consistent with this proposal, because a putative competition for histone acetylases does not explain why NF-B binding to the E-selectin enhancer is also reduced in arterial versus venous ECs in organ culture or in KLF2 transductants. However, the difference between HUAECs and HUVECs in situ in the TNF-induced binding of p300 does appear more profound than the difference in NF-B binding to the E-selectin enhancer.…”
Section: Discussionmentioning
confidence: 57%
“…It has been proposed that KLF2 can bind p300 and compete with phosphorylated NF-B p65 antagonizing NF-B transcriptional activity. 8,10,32 Our ChIP data are not fully consistent with this proposal, because a putative competition for histone acetylases does not explain why NF-B binding to the E-selectin enhancer is also reduced in arterial versus venous ECs in organ culture or in KLF2 transductants. However, the difference between HUAECs and HUVECs in situ in the TNF-induced binding of p300 does appear more profound than the difference in NF-B binding to the E-selectin enhancer.…”
Section: Discussionmentioning
confidence: 57%
“…Myocyte enhancement factor 2 has also been found to bind the Ϫ138/Ϫ111 promoter region in T cells (25). We have also demonstrated that this same region binds several other factors to induce KLF2 expression in macrophages, including hnRNP-D, hnRNP-U, PCAF, and p300 (26). The full complement of trans-acting factors is not known, however; nor is the complete mechanism of activation fully understood.…”
mentioning
confidence: 84%
“…DNA Affinity Chromatography and Mass Spectrometry-DNA affinity chromatography and mass spectrometry were performed as described previously (26) with the exception that complimentary strands of the 62-bp region of the KLF2 promoter (nucleotides Ϫ157 to Ϫ95) were annealed and cross-linked to Sepharose beads. Following washing and incubation in DNA binding buffer, 10 mg of nuclear extract was incubated with the beads for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…24,[33][34][35] This consideration, taken together with the (A) Endothelial cells were transfected with expression vectors containing scrambled DNA (Scr DNA, control) or KLF2, and/or CBP/p300. All cells were also transfected with an NF-B-luciferase reporter and Renilla luciferase.…”
Section: Inhibition Of Nf-b Activity In Apla/␤ 2 Gpi-treated Huvecs Bmentioning
confidence: 99%